ChemInform Abstract: Transporting and Shielding Photosensitisers by Using Water‐Soluble Organometallic Cages: A New Strategy in Drug Delivery and Photodynamic Therapy. Issue 39 (5th September 2013) - Therrien, Bruno
Abstract Review: 50 refs.